Clinicopathological analysis of 5146 eyelid tumours and tumour-like lesions in an eye centre in South China, 2000–2018: a retrospective cohort study. Issue 1 (26th January 2021) - Wang, Linyan; Shan, Yi; Dai, Xizhe; You, Na; Shao, Ji; Pan, Xiangji; Gao, Tao; Ye, Juan
Abstract : Objectives: To describe the clinicopathological characteristics of patients with eyelid tumours and tumour-like lesions in South China, investigate possible factors affecting tumour constitution. Design: Retrospective cohort study. Setting: All patients diagnosed with eyelid tumours were included from a high-volume tertiary eye care centre from South China which caring for over 2000 patients per day. All biopsied specimens were reviewed by two senior pathologists and were classified according to the fourth edition of the WHO Classification of Skin Tumours. Participant: A total of 5146 cases of eyelid lesions were reviewed from 2000 to 2018, being classified by histogenesis and pathologic diagnosis, being compared with data from previous literature containing different races. Main outcome measures: Age-specific and gender-specific incidence constitutions, time trends, tumour location, distribution in different age groups and relationship with Sociodmographic Index (SDI) were calculated. Results: Benign tumours accounted for 85.08% (4378) of all cases, among which, nevus was most common (33.07%). Eight of top 10 benign lesions had higher occurrence in upper eyelids. The R² value of linear regression in patient annual number of benign lesions were 0.946 (p<0.01) for male and 0.914 (p<0.01) for female. More than 33.60% (1471/4378) were made up by patients younger than 40 years. The number of patients undergoing removal of benign lesions decreased with age. Among the malignant lesions, basal cell carcinoma (BCC) was most prevalent (48.70%), followed by sebaceous gland carcinoma (34.24%) and majority (81.8%) occurred in patients above 60 years. Conclusions: Over the past 19 years, most eyelid tumours occurred at our centre were benign lesions. The number of patients presenting with benign lesions increased in both genders, especially among young females who were more likely to request surgeries. Among malignant lesions, BCC remains the most common type, appears a higher incidence in countries with higher SDI.